Application of 5G Mobile Communication Technology Integrating Robot Controller Communication Method in Communication Engineering. (8th April 2023) - Chen, Yu
Abstract : Following the ongoing advancement of the communication industry, data traffic and information have achieved rapid growth. As the core technology of contemporary mobile communication, 5G technology can not only meet the transportation needs of massive data traffic but also be expanded to various industries, expanding the development field of intelligent communication and realizing further improvement of production efficiency. At present, 5G mobile communication technology is widely used in communication engineering, providing effective technical support for engineering construction and operation. However, while the progress of the times brings innovation and refinement in mobile communication technology, it also increases the complexity of market development, in this context, the practical application of 5G technology in communication engineering is limited, which limits the development of both. In order to solve this dilemma, this paper integrated the communication method of the robot controller, and based on the analysis of the characteristics and application status of mobile communication technology, the application of 5G technology in communication engineering was deeply studied. In order to prove the effect of the robot controller communication method, in this paper, simulation experiments were carried out to analyze the application effect of 5G in communication engineering from three aspects of throughput rate, energy efficiency, and signal suppression effect and to compare it with traditional communication methods. The results of the signal suppression experiment showed that the average peak value of the signal under the traditional communication method was 18.134 dB, and the average peak value of the signal under the method in this paper was 11.296 dB, which showed that the 5G technology integrating the communication method of the robot controller is more practical in communication engineering.